POSITIVE VERSUS NEGATIVE COMMUNICATION STRATEGIES IN TASK-BASED LEARNING - Rohani, Siti (TEFLIN Journal, 2013)
This study aimed at describing how the implementation of Task- Based Learning (TBL) would shape or change students' use of oral communication strategies. Students' problems and strategies to solve the problems during the implementation of TBL were also explored. The study was a mixed method, employing both quantitative and qualitative analysis through multi-methods of questionnaire, interviews, focus group discussion, learning journals, and classroom observation. Participants were 26 second year students of the State Polytechnic of Malang. Data collection was conducted for one semester. Findings show linguistic and non-linguistic problems encountered by students during one-semester implementation of TBL. Students also performed increased use of positive strategies but reduced use of negative strategies after the implementation of TBL.